The Effect of Expectancy, Satisfaction of Product Attributes and System Attributes in Repurchasing Online - Wibawa, Rindu Puspita; Subriadi, Apol Pribadi (Institut Teknologi Sepuluh Nopember, 2019)
The growth of e-commerce in Indonesia at early January 2018, 45% of internet users looking for products or services to be purchased online, 45% users visit online retail stores, and 40% users make purchases of a product or service online. Bank Indonesia estimates the value of e-commerce transactions in 2018 reached 144 trillion rupiahs. Based on data of Badan Koordinasi Penanaman Modal (BKPM), the value of investments in e-commerce and financial technology reaches more than US 5 billion. The critical measure of success factors for online stores is the behavior of repeat purchases by consumers. Expectancy and satisfaction of product attributes and system attributes can be the factors that affect online repurchasing. These factors have a positive effect on online repeat purchase. To deepen the phenomenon of the influence in expectancy and satisfaction on product attributes and system attributes, researchers conducted in-depth analysis using qualitative methods. The qualitative method used is a phenomenological approach so that it can describe general meaning of some individuals about life experiences related to the phenomenon. The result of this research is the implications for e-commerce developers. The implications are based on research findings based on e-commerce users, both buyers and experts in the field of business and communication. The implications hopefully can provide insight into the factors affecting the community to shop online in Indonesia and help e-commerce in Indonesia to improve and expand its business